Smart Solar Panel using Light Dependent Resistors. Issue 1 (December 2020) - Karthik, S; Vivek Karthick, P; Thirrunavukkarasu, R R; Satheesh Kumar, S; Selvakumar, D
Abstract: Solar energy is gradually approaching a most important form of renewable energy. Using solar tracker, additional energy can be produced, since the solar plate can maintain a vertical angle to the sunrays. Given the substantial initial expense of setting up the tracking device, there are less expensive alternatives that have been suggested over period. This paper addresses the strategy and development of solar tracking device prototype which has one axis of independence. Here, Light Dependent Resistors (LDRs) are used to sense the sunlight.